2018
DOI: 10.1016/j.ica.2018.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondria localizing high-spin iron complexes of curcumin for photo-induced drug release

Abstract: We found an error in Fig. 6 showing similarity among few lanes of the gel diagram. The earlier image has been replaced with the corrected one which is given below. This correction does not change the conclusions of the article. The authors would like to apologise for any inconvenience caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Light promoted bond cleavage reactions of photocaged compounds serve as powerful tools to create materials in a highly spatially and temporally controlled manner. As a result, these substances have found wide applications in tissue engineering, biosensing, counterfeit detection, controlled release of functional molecules, and regulation of gene expression. Moreover, owing to their use of noninvasive optical triggers, and its high spatial and temporal precision, photocaged substances have been utilized to explore biological processes and elucidate their mechanistic nature. Arylcarbonylmethyl, nitroaryl ( ortho -nitrobenzyl, ortho -nitroanilides), azobenzene, xanthene, coumarin-4-ylmethyl, and indoline groups , are the commonly used photoreaction triggers to construct photocages for controlled release of metal ions (Ca 2+ , Zn 2+ , Cu 2+ ), drugs, and other bioactive substances. Particularly, incorporation of nitrobenzene derivatives along with metal ion-binding ligands has become a prevailing tool to investigate the signaling processes in biological systems that are governed by metal ions. In addition, photocage containing metal ion complexes along with fluorophores whose optical properties are altered by metal ion binding and release have been employed to elucidate cellular processes and signaling …”
Section: Introductionmentioning
confidence: 99%
“…Light promoted bond cleavage reactions of photocaged compounds serve as powerful tools to create materials in a highly spatially and temporally controlled manner. As a result, these substances have found wide applications in tissue engineering, biosensing, counterfeit detection, controlled release of functional molecules, and regulation of gene expression. Moreover, owing to their use of noninvasive optical triggers, and its high spatial and temporal precision, photocaged substances have been utilized to explore biological processes and elucidate their mechanistic nature. Arylcarbonylmethyl, nitroaryl ( ortho -nitrobenzyl, ortho -nitroanilides), azobenzene, xanthene, coumarin-4-ylmethyl, and indoline groups , are the commonly used photoreaction triggers to construct photocages for controlled release of metal ions (Ca 2+ , Zn 2+ , Cu 2+ ), drugs, and other bioactive substances. Particularly, incorporation of nitrobenzene derivatives along with metal ion-binding ligands has become a prevailing tool to investigate the signaling processes in biological systems that are governed by metal ions. In addition, photocage containing metal ion complexes along with fluorophores whose optical properties are altered by metal ion binding and release have been employed to elucidate cellular processes and signaling …”
Section: Introductionmentioning
confidence: 99%
“…The analogous charge-neutral Fe III complex 191 ( Figure 29 ) and two other high-spin iron complexes reportedly released curcumin upon irradiation with visible light, and thus exhibited cytotoxicity in multiple cell lines. 1056 In addition, Fe III –polysaccharide hydrogels were found to be visible-light (405 nm) responsive because of the photoreduction of the Fe III ions to Fe II , which rendered the Fe complexes incapable of functioning as cross-linkers for the polymer. 1057 …”
Section: Photorelease From Coordination Compoundsmentioning
confidence: 99%
“…Biotin has been established to have a strong binding affinity for protein receptors like avidin and streptavidin (∼10 14 M) [20] . The present work stems from our continued interest towards designing mixed‐ligand iron(III) based anticancer agents for cancer cell targeting and apoptotic cell death [21–24] . Recent studies have indicated that curcumin can modulate different biological processes involved in cell cycle regulation, mutagenesis, tumorigenesis and apoptosis.…”
Section: Introductionmentioning
confidence: 99%